(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Malaki ABB, Alcazar SMT, LILLO EP, Rosales RC, Redoblado BR, DIAZ JL. 2021. Diversity and conservation status of avifauna in Mount Lantoy Key Biodiversity Areas (KBA) in Cebu Island, Philippines. Biodiversitas 23: 671-678. A study on the bird community in Mount (Mt.) Lantoy Key Biodiversity Areas (KBA) was carried out to determine its diversity and conservation status to conserve, protect, and rehabilitate forest habitat within the KBA. The study was conducted across three sampling sites. By using the transect, point count, and mist nets, we found 1,340 individuals belonging to 31 orders, 32 families, and 44 species within the study sites. There were five dominant bird species, i.e., Hypsipetes philippinus (J.R.Forster, 1795), Phapitreron leucotis (Temminck, 1823), Psilopogon haemacephalus (P.L.S.Müller, 1776), Nectarinia jugularis (Linnaeus, 1766), and the endangered Kittacincla cebuensis (Steere, 1890). We also found rare bird species within the study site, such as Haliastur indus (Boddaert, 1783), Geopelia striata (Linnaeus, 1766), Monticola solitarius (Linnaeus, 1758), Oriolus chinensis (Linnaeus, 1766), Dendrocopos maculatus (Scopoli, 1786), Pycnonotus goiavier (Scopoli, 1786), and Rallina eurizonoides (Lafresnaye, 1845). We also found six Philippine endemics, including K. cebuensis, Ninox rumseyi (Rasmussen et al. 2012), H. philippinus, D. maculatus, Loriculus philippensis (Statius Muller, 1776), and Caprimulgus manillensis (Walden, 1875). Based on the IUCN Red List of Threatened Species, two species are Endangered, and 42 species are Least Concern (LC). Using the "Checklist of the Birds of the Philippines," we found two species are Endangered, two species are Near Threatened, and 40 species are LC. The diversity of birds in Mt. Lantoy KBA was moderate. We considered that this KBA is highly exposed to various forest or habitat disturbances such as land-use conversion, charcoal making, firewood gathering, slash-and-burn method of cultivation, and infrastructure development. There is a need to strictly implement the policies governing the utilization of forest resources to augment the diversity of the study site.